IMPLEMENTASI MANAJEMEN LEARNING CIRCLE ANTAR GENERASI GURU UNTUK PENGEMBANGAN BUDAYA BERBAGI PENGETAHUAN DI SMA NEGERI 3 CIREBON - Septiana, Azis; Cahyani, Dewi; Suklani (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the implementation of intergenerational Learning Circle management in developing a culture of knowledge sharing among teachers at SMA Negeri 3 Cirebon. The Learning Circle program, known as Entog Cup Ekek, serves as a collaborative platform for senior and junior teachers to exchange best practices, present innovative learning models, and develop technology-based and AI-assisted assessments. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis. The findings show that the implementation of the Learning Circle operates through structured stages of planning, collaborative execution, and reflective evaluation, enabling systematic knowledge transfer. The culture of knowledge sharing across generations has strengthened, indicated by increased openness, active participation, and routine discussions of pedagogical innovations across MGMP subject groups. The program also positively impacts professional collaboration, reduces intergenerational barriers, and minimizes competency gaps—particularly in pedagogical and digital skills-between senior and junior teachers. These findings indicate that the Learning Circle can function as an effective knowledge management model that enhances teacher professionalism and fosters a collaborative school culture.